Acute chest syndrome in pediatric sickle cell disease: A 19-year tertiary center experience - Abdullah A Yousef; Hwazen A Shash; Ali N Almajid; Ammar A Binammar; Hamza Ali Almusabeh; Hassan M Alshaqaq; Mohammad H Al-Qahtani; Waleed H Albuali (Annals of Thoracic Medicine, 2022)
INTRODUCTION: The most common cause of death among sickle cell disease (SCD) patients is acute chest syndrome (ACS). Since SCD is a common condition in the Eastern province of the Kingdom of Saudi Arabia (KSA), we aimed to provide a detailed description of the clinical characteristics and ACS management. METHODS: We retrospectively studied pediatric (<14 years) patients with SCD diagnosis who were admitted with ACS or developed ACS after admission from January 2002 to December 2020. The absence of chest X-ray or hemoglobin electrophoresis was the reason to exclude patients from the study. The primary objective of the study was to evaluate and report the clinical, laboratory, and management characteristics of ACS. RESULTS: Ninety-one ACS episodes (42 patients) were included, with a mean diagnosis age of 7.18 ± 3.38 years. Twenty-two (52.4%) patients were male. Twenty-five patients had recurrent ACS episodes. The median absolute number of ACS was 3.5 (interquartile range [IQR], 2–9), with maximum ACS episodes of 13/1 year and a minimum of 1 ACS episode per year. At the first ACS episode, the mean age was 6.62 ± 3.38 years, while the overall mean age at ACS episode diagnosis was 7.18 ± 3.38 years. The most common antecedent events were vaso-occlusive crisis (12 episodes, 13.2%) and upper respiratory tract infections (8 episodes, 8.8%). The most frequently encountered presenting symptoms were fever (70.3%) and cough (70.3%). The most common antibiotics used were azithromycin (82.4%) and ceftriaxone (75.8%). Nine patients (9.9%) required pediatric intensive care unit (PICU) admission. Of the 91 ACS episodes, there was no in-hospital mortality. The median hospital and PICU length of stay were 8 days (IQR, 5–10.25) and 4 days (IQR, 3–5.5), respectively. CONCLUSION: This study has reported the most common clinical characteristics and management of ACS among pediatric SCD patients in the Eastern province of KSA.